1985
DOI: 10.1128/mcb.5.11.3316
|View full text |Cite
|
Sign up to set email alerts
|

Antibody of predetermined specificity to a carboxy-terminal region of H-ras gene products inhibits their guanine nucleotide-binding function.

Abstract: The high prevalence of ras oncogenes in human tumors has given increasing impetus to efforts aimed at elucidating the structure and function of their p21 products. To identify functionally important domains of the p21 protein, antibodies were generated against synthetic peptides corresponding to various regions of the protein. Antibodies directed against a synthetic peptide fragment corresponding to amino acid residues 161 to 176 in the carboxy-terminal region of the H-ras-encoded p21 molecule specifically rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The functional connection between this lipid modification and Ras function was made by Douglas Lowy’s group in 1984, which showed that lipid binding and membrane association were actually required for the transforming activity of the viral H-Ras oncoprotein 49,50 . working with cellular H-Ras, Stuart Aaronson’s group proceeded to demonstrate that this C-terminal processing and membrane recruitment of Ras is a prerequisite to its biochemical activation 51 .…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…The functional connection between this lipid modification and Ras function was made by Douglas Lowy’s group in 1984, which showed that lipid binding and membrane association were actually required for the transforming activity of the viral H-Ras oncoprotein 49,50 . working with cellular H-Ras, Stuart Aaronson’s group proceeded to demonstrate that this C-terminal processing and membrane recruitment of Ras is a prerequisite to its biochemical activation 51 .…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…However, these studies indicate the biochemical reactivity of the polyclonal sera with their respective proteins was only fair at best and in the case of one polyclonal sera it was reported not to react with the p21 at all. Additional studies have reported antisera to the amino acid sequence 161-176 of the Ha-ras p21 (13) while another report describes antisera raised to a synthetic peptide representing amino acids 171-186 of the Ki-ras p21 (14).…”
Section: Discussionmentioning
confidence: 97%
“…To date, there have been several reports describing polyclonal sera to the individual Ha, Ki and N-ras p21 (12)(13)(14)(15). However, the limited availability of these reagents and the inconsistencies that exist between the different polyclonal sera have restricted investigations of the Ha, Ki and N-ras p21.…”
Section: Introductionmentioning
confidence: 97%
“…As yet, there has been only indirect evidence concerning the biologic importance of GTP binding in p21 function as well as the localization of GTP-binding site(s) within the p21 molecule. Such studies have relied for the most part on antibodies which inhibit biochemical activities of purified bacterially expressed ras proteins . Srivastava et al, 1985 or affect the phenotype of ras proteins expressing cells upon microinjection .…”
Section: Introductionmentioning
confidence: 99%